Applications and Future Perspectives of CRISPR/Cas9 Gene Editing Technologies in CAR-T Cell Therapy - Menghan Liu (International Journal of Biology and Life Sciences, 2026)
A recent major breakthrough in cancer immunotherapy is the Chimeric antigen receptor-T cell (CAR-T cell) therapy, which has shown significant clinical efficacy in haematological malignancy treatment. Nonetheless, its application in a more general way is limited by a number of challenges, such as T-cell exhaustion, off-target associated toxicities, and the difficulty of personalised manufacturing. Recently, new opportunities have come into solving these problems with the introduction of clustered regularly interspaced short tandem repeats (CRISPR)-Cas9 genome editing, which has made it possible to perform precise and combinatorial genetic editing in CAR-T cells. The important applications of CRISPR in CAR-T cell engineering, which include the disruption of inhibitory immune checkpoints to enhance antitumour activity, the generation of universal allogeneic CAR-T cells by deletion of T-cell receptor and human leukocyte antigen (HLA) genes, and the modulation of cytokine signalling pathways to reduce toxicity are discussed in this review. Moreover, novel approaches, including targeted CAR integration and multiplex gene editing, are discussed as having the potential to enhance the therapeutic efficacy and scalability. In spite of these improvements, there are issues of off-target effect, delivery efficacy, genomic instability, and unaddressed issues of long-term safety. CAR-T cell therapies are likely to be improved further in future through advancements in genome editing technology, delivery methods, and synthetic biology. In general, CRISPR/Cas9-based engineering is a promising way of developing the next generation of precision cancer immunotherapy.